State Asset Management in the Framework of Good Governance and International Law for Sustainable Development - Syamsir, Syamsir; Nuriyatman, Eko; Saraya, Sitta; Arifin, Firdaus; Qutieshat, Enas (Jambura Law Review, 2026)
State asset management is a core function of public law through which the State exercises authority over public resources to support sustainable development. In modern international legal discourse, state assets are no longer viewed merely as economic tools but as legal objects governed by international obligations and good governance principles. This article examines the international legal framework on state asset management and its relevance to strengthening asset governance in Indonesia using a normative legal research approach that analyzes both international and national legal instruments, with particular attention to the interaction between soft law and hard law. It reviews key frameworks such as the Sustainable Development Goals, the Paris Agreement, the International Covenant on Economic, Social and Cultural Rights, and the United Nations Convention against Corruption, and evaluates their alignment with Indonesia’s domestic regulations through library research and qualitative analysis using systematic and teleological interpretation. The study finds that while soft law provides important normative guidance for sustainability-oriented governance, excessive reliance on non-binding mechanisms risks weakening legal certainty and accountability; therefore, binding regulations grounded in good governance principles transparency, accountability, public participation, and the rule of law are essential to ensure that state assets function effectively as instruments of sustainable development. From an ius constituendum perspective, aligning international commitments with enforceable domestic law is necessary to protect public interests, ensure intergenerational equity, and promote sustainable national development.